EFFECT OF POWER ULTRASOUND ON VIBRIO SPP. DISINFECTION - Cường, Nguyễn Văn; Thảo, Nguyễn Thị Xuân; Chương, Trương Văn; Dũng, Lê Quang Tiến (Hue University Journal of Science: Natural Science, 2017)
This paper presents the results of the application of power ultrasound to disinfect Vibrio spp. The results showed that the 150 W power ultrasound with a frequency of 26 kHz can disinfect Vibrio spp. quite effectively. On the other hand, the combination of the ultrasound (26 kHz, 150 W) and the oxidizing agent H2O2 can significantly improve Vibrio spp. disinfection.